The Importance of Work Culture on Job Satisfaction and Good Governance in the Transportation Industry - Adam , Abdul-Kahar; Asaadi, Nasser Al; Sulemana, Ebi Shahrin Bin (International Journal of Psychosocial Rehabilitation, 2020)
This is theoretically basic research with conceptual studies theories to establish the importance of work culture in an organisation. Work Culture is seen as the behaviours, attitudes, commitments and staff performance are key in advancing towards orgnisational objectives. Work Culture have direct correlation with job satisfaction and good governance and that is if organisations really want to grow their business. Job satisfaction on the other hand states that both extrinsic and intrinsic factors such as the salary increment and employees’ welfare are paramount to the hearts of staff. Moreover, good governance demands that the following principles must be put into practice namely accountability, integrity, compliance, trustworthy, discipline, ethical leadership, efficiency and effectiveness, and participation. In the methodology, a random sample of 40 public bus drivers were interviewed with their responses used to generate data for analysis in SmartPLS. The results indicated that all the three (3) variable constructs are valid and reliable. The Cronbach Alpha for Job Satisfaction, Good Governance, and Work Culture was 0.7, 0.8, and 0.7 consecutively. According to Hair et al., (2007) argued that a Cronbach alpha value of 0.6 and above means there is high reliability. This was a quantitative research study. This conceptual research showed that in the transport industry especially the public sector more attention must be paid to these three variables in order to achieve objectives namely good governance, job satisfaction and work culture to improve the human resource management practices in the public transportation industry. The model tested was complete mediation as in figure 4 depicted.